Pengaruh Kompetensi dan Pelatihan Kerja terhadap Kinerja Pegawai Negeri Sipil pada Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Kabupaten Bungo - Desmalia Desmalia; Darham Wahid; Herawati Herawati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the impact of understanding the influence of Competence and Job Training on the Performance of Civil Servants at the Public Works and Spatial Planning Office of Bungo Regency. A sample of 44 respondents was selected using the Random Sampling technique. Based on the data processing results using the SPSS Application, it was found that competence has a significantly positive effect on the performance of Civil Servants at the Public Works and Spatial Planning Office of Bungo Regency. Job Training affects the Performance of Civil Servants at the Public Works and Spatial Planning Office of Bungo Regency. Meanwhile, Competence (X1) and Job Training (X2) have a significant positive impact together (simultaneously) on the Performance (Y) of Civil Servants at the Public.